Functioning assessment vs. conventional medical assessment: a comparative study on health professionals' clinical decision‐making and the fit with patient's own perspective of health. Issue 7 (2nd July 2013) - Stallinga, Hillegonda A; Roodbol, Petrie F; Annema, Coby; Jansen, Gerard J; Wynia, Klaske
<x xml:space="preserve">Abstract</x> Aims and objectives To compare a functioning assessment based on the International Classification of Functioning, Disability and Health (ICF) with a conventional medical assessment, in terms of their respective consequences for health professionals' clinical decision‐making and the fit with patient's own perspective of health. Background In chronic diseases, pathogenic‐oriented health care falls short in generating all the information required for determining healthcare provision to improve health. A broader, so‐called salutogenic approach, by using the ICF, focusing on how to stay healthy, rather than on what causes diseases, seems more appropriate. Design A cross‐sectional comparative study using data from a randomised controlled trial. Methods Data about patient problems and professional healthcare activities were collected from a total of 81 patients with severe multiple sclerosis who were randomly assigned to one of two groups: the ICF group, assessed with a functioning assessment (n = 43), and the medical group, assessed with a conventional medical assessment (n = 38). Data were analysed statistically using descriptive and inferential statistics. Results A functioning assessment resulted in the registration of significantly more patient problems in the health components 'participation' and 'environmental factors', as well as significantly more professional healthcare activities befitting these components. The ICF group had a significant positive correlation between registered problems by health professionals and patients' self‐reported problems, whereas the medical group had several negative correlations. Conclusion A functioning assessment resulted in a care plan that not only was broader and more complete but also reflected the patients' self‐reported problems more closely than a medical assessment, without a loss of focus on medical problems. Relevance to clinical practice This study has shown that some health problems remain unnoticed by a medical assessment alone, which is especially important for the chronically ill. A functioning assessment provides a strong foundation for identifying all relevant information related to health.